Belajar dari semut dan lebah: Hikmah kehidupan dari kerja keras dan kerjasama - Mufidah, Do'aul Isma (Maliki Interdisciplinary Journal, 2024)
The purpose of this article is to describe and explain the wisdom of Allah's creatures, ants and bees. Nowadays all problems come in various forms. For Muslims, the Qur'an is a guide to life. The Qur'an contains solutions to the problems that humans face. It takes a scientific discipline to understand the Qur'an, the discipline is the science of interpretation. From time to time, the science of interpretation is always developing. The insight of tafsir becomes very much to be discussed and studied. One of the interesting things to study is in the field of science. Science is a very rapidly growing field at this time. It turns out that science has a relationship with Islam. Here tafsir serves to see science in an Islamic perspective. Such as revealing the goodness of various living things that exist around humans themselves. Animals in human life act as extras to serve humans as leaders on earth, but it turns out that in the Qur'an animals are used as a lesson for humans. Animals as an intermediary for Allah to show the beauty of his creation, such as bees that can produce honey that is rich in benefits and ants with their uniqueness in socialising.